The Function of Taboo Expressions in Nicki Minaj’s Song Lyrics - Anindita Dewangga Puri; Theodora Pramasitha Yudanti; Owena Zaneta Yogaswari (Universitas Sanata Dharma, 2024)
The societal phenomenon of taboo terms is commonly expressed in song lyrics. This research focuses on the function of taboo expressions in the song lyrics of Nicki Minaj, a singer who is known to use such expressions. The first objective of this analysis is to determine the types of taboo expressions found in Minaj’s songs. Secondly, the researchers examine the function of these expressions in the song lyrics. Four of Minaj's songs are presented in the data: